Pelaksanaan Peraturan Desa Nomor 03 Tahun 2023 TentangPerubahan Anggaran Pendapatan Dan Belanja Desa Pamijen TahunAnggaran 2023 Kecamatan Sokaraja Kabupaten Banyumas - Afrina Mayang W; Wahyu Hariadi; Haris Kusumawardana; Esti Ningrum (Wijayakusuma Law Review, 2024)
The village as the smallest governmental entity, plays a crucial role in regional autonomy, with the readiness of thevillage in establishing its governance system impacting the development anda welfare of its community. Themanagement of village finances, especially the Village Revenue and Expenditure Budget (APBDes), is crucial insupporting village development. This research aims to understand how the implementation of Pamijen VillageRegulation Number 03 of 2023 concerning the Amendment of the Pamijen Village Revenue and Expenditure Budgetfor the Fiscal Year 2023 in Sokaraja Subdistrict, Banyumas District, and to identify the challenges faced in theimplementation of Pamijen Village Regulation Number 03 of 2023 concerning the Amendment of the PamijenVillage Revenue and Expenditure Budget for the Fiscal Year 2023 in sokaraja Subdistict, Banyumas District. Themethodological approach used is normative juridical with descriptive analysis. Date were obtained from fieldstudies at the Pamijen Village Office and trough interviews with villagr officials. The research findings indicate thatthe implementation of APBDes in Pamijen Village complies with applicable regulations. However, there aretechnical constraints and budget changes that affect activity realization. It is recommended that the villagegovernment continue to evaluate and minimize constraints in the implementation of APBDes. This research isexpected to contribute to the development of knowledge, particularly in the context of village financial managementKeywords: Implementation, Village Regulation, APBDe